Association between Age and New Onset Ischemic Stroke in Diabetic Patients (Bangladesh Journal of Neuroscience, 2017)
Background: Ischemic stroke is the end result of occlusion of a blood vessel supplying the brain by a thrombus originating somewhere outside the brain or as a result of a thrombotic stenosis of a cerebral blood vessel itself. Older people have higher prevalence of ischemic stroke.Objective: To evaluate the association between higher age and new onset ischemic stroke in patient with diabetes mellitus.Method: This cross sectional study was conducted in the Department of Neurology, BSMMU, Dhaka from February 2013 to September 2014 on 50 DM patients with first attack of ischemic stroke. mRS was measured on 14th day of the stroke.Result: Majority of the patients (40.0%) were in age group 51-60 years. The mean age was 58.9 ± 9.6 years with a range from 30 to 75 years. Males were 52.0% and females were 48.0%. Male to female ratio was 1.08:1. It was observed that more than one third (36.0%) patients were current smoker, 9(18.0%) were ex-smoker and 23(46.0%) were non smoker. Majority of the patients, 29(58.0%), had hypertension. Mean systolic BP was found 129 ±16 mmHg with a range from 90 to 160 mmHg. The mean diastolic BP was found 81±11 mmHg with a range from 60 to 100 mmHg. Age has significant positive correlation with modified ranking scale on 14th day of stroke [r= 0.322 (p=0.023)].Conclusion: As per study result, it can be concluded that increasing age is associated with higher level of mRS.Bangladesh Journal of Neuroscience 2017; Vol. 33 (1): 1-5